Quem pensa no futuro poupa mais? O papel mediador do conhecimento financeiro na relação entre orientação para o futuro e segurança financeira pessoal - Gonçalves, Virgínia Nicolau (2017)
Saving is a behavior that contributes to financial security. However, low savings rates characterize several societies, particularly the Brazilian one, and are associated with financial vulnerability. Choices between saving and spending are influenced by both economic and psychographic characteristics. In this context, the main objective of this study is to evaluate the relationship between financial knowledge and the orientation towards the future in the level of personal financial security. In addition, the study assesses whether financial knowledge is a mediating variable in the relationship between orientation towards the future and financial security. An online survey was conducted with 378 participants aged 25-50. The analysis of the mediation model revealed that the greater the orientation towards the future, the greater the interest in financial knowledge and the greater the financial security. The study concluded that time orientation influences individuals' saving behavior and increases the propensity to search for financial knowledge. These results are relevant for the adaptation of financial education programs for public and private institutions, since they highlight the importance of raising people's awareness of future orientation prior to exposure to financial education content. Implications are also offered for academics, managers and policy makers, as well as possibilities for future research.